2009
DOI: 10.3892/ijmm_00000175
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate-induced alterations of phosphoinositide metabolism, protein kinase C activity and reduced CD44 variant expression in HT-29 colon cancer cells

Abstract: Abstract. Initiation of cell growth and neoplastic transformation frequently involves activation of growth factor receptor-coupled tyrosine kinases and stimulation of the phosphoinositide second messenger system. Altered expression of CD44 variants was reported in several malignant tumor types with possible implications for tumor progression and prognosis. CD44 variant expression was reported to be associated with second messenger activation and differentiation. We therefore investigated the effects of butyrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…MSH2 gene was up-regulated (9.8-fold) by FE-hgf-LC 50 extract supporting its involvement with DNA repair in accordance with earlier observations (Hoeijmakers, 2001;Lyer, Pluciennik, Burdett, & Modrich, 2006;Peltomäki, 2001Peltomäki, , 2003. Several studies (Emenaker et al, 2001;Hinnebusch, Meng, Wu, Archer, & Hodin, 2002;Hofmanová, Vaculová, Lojek, & Kozubík, 2005;Koop, Fichter, Assert, Pfeiffer, & Classen, 2009;Li, Luo, Paul, Tang, & Yuan, 2006) suggest that the production of butyrate in the colon may be protective against colon carcinogenesis. Current studies and clinical trials (Archer et al, 2005;Butler et al, 2001;Cucciolla et al, 2008;He et al, 2001;Law, Lai, Lui, Wan, & Wong, 2008;Marks, Rifkind, Richon, & Breslow, 2001) strongly suggest that histone deacetylace inhibitors (HDAC) such as trichostatine (TSA), butyrate and suberoylanilide hydroxamic acid, which also induce p21Waf1/Cip1 expression, are effective in arresting cancer cell proliferation and lead to cells undergoing differentiation (as in acute promielocytic anemia) or apoptosis.…”
Section: Apoptosissupporting
confidence: 87%
“…MSH2 gene was up-regulated (9.8-fold) by FE-hgf-LC 50 extract supporting its involvement with DNA repair in accordance with earlier observations (Hoeijmakers, 2001;Lyer, Pluciennik, Burdett, & Modrich, 2006;Peltomäki, 2001Peltomäki, , 2003. Several studies (Emenaker et al, 2001;Hinnebusch, Meng, Wu, Archer, & Hodin, 2002;Hofmanová, Vaculová, Lojek, & Kozubík, 2005;Koop, Fichter, Assert, Pfeiffer, & Classen, 2009;Li, Luo, Paul, Tang, & Yuan, 2006) suggest that the production of butyrate in the colon may be protective against colon carcinogenesis. Current studies and clinical trials (Archer et al, 2005;Butler et al, 2001;Cucciolla et al, 2008;He et al, 2001;Law, Lai, Lui, Wan, & Wong, 2008;Marks, Rifkind, Richon, & Breslow, 2001) strongly suggest that histone deacetylace inhibitors (HDAC) such as trichostatine (TSA), butyrate and suberoylanilide hydroxamic acid, which also induce p21Waf1/Cip1 expression, are effective in arresting cancer cell proliferation and lead to cells undergoing differentiation (as in acute promielocytic anemia) or apoptosis.…”
Section: Apoptosissupporting
confidence: 87%
“…We previously showed, that the expression of CD44 variant isoforms is stimulated by growth factors like PDGF or IGF-I and regulated by phospho-inositide 3-kinase and protein kinase C in SK-N-SH human neuroblastoma cells (18). Recently, we reported, that sodium butyrate, a potent HDAC inhibitor, known to regulate intestinal epithelial cell proliferation and differentiation, reduced the expression of high molecular CD44v3, v5 and v8 variants in HT-29 colon carcinoma cells (29). Similar findings were reported by Barishat et al in HM7 colon carcinoma cells showing decreased expression of CD44 variants and reduced metastatic potential following butyrate treatment, indicating an association of CD44 variant overexpression with hyperproliferative and undifferentiated cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…This area of research has implicated cancer stem cells (CSCs), microRNA (miRNA) and genetic mutations as markers of the development of CRC. Studies have identified CD44 as a specific marker for CSCs and have also found several CD44 splice variants, some of which correlated well with colon cancer progression [11][12][13]. Our previous study reported increased expression of CD166 with CD44 to be associated with colonic carcinogenesis.…”
Section: Introductionmentioning
confidence: 72%